Semi-crystalline terpolymers with varying chain sequence structures derived from CO2, cyclohexene oxide and ε-caprolactone: one-step synthesis catalyzed by tri-zinc complexes. Issue 9 (18th December 2014) - Xu, Yonghang; Wang, Shuanjin; Lin, Limiao; Xiao, Min; Meng, Yuezhong
Abstract : Novel semi-crystalline terpolymers with varying chain sequence structures derived from cyclohexene oxide (CHO), CO2 and ε-caprolactone (CL) were synthesized and reported. Abstract : Novel semi-crystalline terpolymers with varying chain sequence structures derived from cyclohexene oxide (CHO), CO2 and ε-caprolactone (CL) have been firstly synthesized and reported. The terpolymerization is catalyzed by Schiff base tri-zinc complexes via a one-step route. The tri-zinc complexes also exhibit a very high catalytic activity for the homopolymerization of ε-caprolactone in the absence of CHO. A series of terpolymers with varying content of crystalline segments are produced by adjusting the feedstock ratio of CHO/ε-CL. The reactivity of different monomers was investigated by experimental methodology. The results indicate that ε-CL is much more active than CHO in this terpolymerization system. Therefore, the incorporation of ε-CL can dramatically improve the TONs of terpolymer containing ε-CL moieties. Moreover, the thermal properties of the resulting terpolymers were also studied by DSC and TGA. Finally, the polymerization mechanism of this ternary system is extensively discussed based on experimental phenomena. To the best of our knowledge, this is the first report on novel catalysts capable of synthesizing polycarbonates, polyesters and poly (carbonate-ester) via a one-step polymerization.